A review of the New World Coproica (Diptera: Sphaeroceridae) with a description of 8 new species - Bergeron, Matthew D.; Marshall, Stephen A.; Swann, John E. (Zootaxa, 2015)
The New World species of Coproica Rondani, 1861 (Diptera: Sphaeroceridae) are reviewed on the basis of over 17,000 examined specimens. The genus is divided into three major clades: the C. acutangula, C. vagans, and C. urbana species groups. Eight new species (C. bifurcata, C. bispatha, C. brachystyla, C. diabolica, C. emarginata, C. galapagosensis, C. novacula, and C. testudinea) are described, and redescriptions are provided for eleven additional species. Included are two keys (one for the twenty New World species only and one for all described species), updated New World distribution records, and illustrations of male and female genitalic structures.